Evaluation of the Dawson College shooting psychological intervention: moving toward a multimodal extensive plan - Bleau, Pierre (Psychological trauma, 2013)
In 2006, following the shooting at Dawson College, the authorities implemented an intervention plan. This provided an opportunity to analyze the responses to services offered, and afforded a learning opportunity, which led to the proposal of an extensive multimodal short- and long-term psychological plan for future needs. Both quantitative and qualitative data were gathered 18 months after the event, involving the participation of 948 students and staff. Mental health problems and the perception of services offered after the shooting were investigated, using standardized measures. Second, focus groups and individual interviews were conducted among a subgroup of participants (support team members; teachers and employees; students and parents) and permitted to gather data on services received and services required. Individual report of events, the extent of psychological impact and services offered and received were analyzed in terms of the following dimensions: intervention philosophy, training, ongoing offer of services and finally, detection and outreach. A significant incidence of disorders and a high rate of exacerbation of preexisting mental disorders were observed within the 18 months following the shooting. Postimmediate and short-term intervention appeared adequate, but the long-term collective vision toward community support and availability of mental health services were lacking. Lessons learned from this evaluation and other school shootings suggest that preparedness and long-term community responses are often overlooked. A multimodal extensive plan is proposed based on a theoretical model from which interventions strategies could be drawn